Energy Justice Through Solar: Constructing and Engaging Low-Income Households - Si, Yutong; Stephens, Jennie C. (Frontiers in Sustainable Cities, 2021)
Minimal research has assessed the policy process of developing solar programs at the state level, and no research yet has investigated how these policies characterize and engage with the target populations they are designed to benefit. Grounded in Schneider and Ingram’s social construction framework (SCF) and applying computational methods (i.e., text analysis and machine learning), this research examines how low-income households are socially constructed in policy provisions, how their social construction has been reinforced through public participation, and how to classify low-income households among target populations. Based on the case of Massachusetts, this research analyzes the 2020 Solar Massachusetts Renewable Target (SMART) Emergency Regulation as well as its public comments. We find that low-income households constitute a visible target group of this program and their characterization as “deserving policy benefits” are positively constructed by policy makers. Furthermore, the conveyed messages and attitudes regarding the assigned benefits to low-income households have been reinforced through public participation. Despite this advantageous positive construction, low-income households have less political power (i.e., measured by topic prevalence in the public comments) than other target groups such as large corporations (e.g., solar developers or solar installers) and less ability to participate or be represented in the policy process, making their voices less likely to be heard by policy makers. With positive social construction but weaker political power, low-income households fall into the category of “dependents” instead of “advantaged,” which may engender undesirable policy outcomes minimizing the intended long-term benefits of the policies to low-income households. This research reveals procedural injustices in energy policies and highlights the importance of more inclusive policy-making process, while also offering a novel theoretical lens to understand the rationale and dynamics of developing solar statutes targeting low-income households.